Effect of pre-treatment of Food waste on lipid production of the two oleaginous yeast strains Cryptococcus curvatus 2698 and Yarrowia lipolytica 35 - Arjunan Umapathi; Kumarasamy Murugesan; Ammaiyappan Selvam (The Bioscan, 2025)
A batch experiment was conducted to study the effect of different pretreatment methods of food waste (FW) on the growth and lipid accumulation of two oleaginous yeasts Cryptococcus curvatus 2698 and Yarrowia lipolytica 35. Food waste was pretreated by acid (A), thermal (T) and acid-thermal (AT) hydrolysis methods. The resulting FW filtrate, without any nutrient supplementation, was used as culture medium for both the yeasts. Compared to other pretreatment methods, acid-thermal hydrolysis method solubilized more carbon content from the food waste material. This higher carbon content of FW-AT medium supported higher biomass production of the yeast strains C. curvatus (10.35 ± 0.51 g/L) and Y. lipolytica (9.80 ± 1.2 g/L). Compared to Y. lipolytica, higher lipid content was obtained from C.curvatus from the acid treated food waste medium (8.81 ± 1.17 %, g/g). It was observed that the culture medium from food waste with acid-thermal pretreatment is suited for biomass production and food waste with acid pretreatment medium enhanced the lipid production among the other treatments.